A particular behaviour of egg-bearing females observed in Micropeplus fulvus Erichson (Coleoptera Micropeplidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
Some 20 adults of this species were selected in October from masses of plant debris and breaded in jars with pieces of fungal fruiting bodies. Within the following November, females scattered several eggs on the jar ground and did covered each of them with a layer of faeces. Although they emerged 6-7 days later, larvae did not moult and died within a few days. Therefore, number of instars (3 items) was evaluated on specimens previously collected in the field. Because M. fulvus females do protect their eggs with an excretion (not a secretion), they exhibit a type of parental care unreported for Coleoptera. Elsewhere, females do use either thesilk arising from calices, as in most Hydrophiloidea, or the abdominal secretion of particular glands of abdomen, as in Mastigus pilifer Kraatz (Scydmaenidae).
Keywords: oviposition; parental cares; faecal protection